Psychological and Pedagogical Practice in the Education System (Results of the All-Russian Contest of the Best Psychological and Pedagogical Programs and Technologies in the Educational Environment – 2021) - Rubtsov, V.V.; Romanova, E.S. (Bulletin of Practical Psychology of Education, 2022)
The article discusses the results of the analysis of the programs of participants in the All-Russian Contest of the best psychological and pedagogical programs and technologies in the educational environment – 2021. The programs submitted for the contest had to meet a large set of requirements related to the professional level and creative potential of educational psychologists in Russia. The analysis of the experience of implementing regional programs for the provision of psychological and pedagogical assistance to children is aimed at improving the scientific and methodological support of psychological and pedagogical activities. The number of programs and technologies submitted for the contest demonstrates the place and role of correctional, developmental, preventive and educational work of educational psychologists. В статье обсуждаются результаты анализа программ участников Всероссийского конкурса лучших психолого-педагогических программ и технологий в образовательной среде — 2021. Представленные на конкурс программы должны были отвечать большому набору требований, связанных с профессиональным уровнем и творческим потенциалом психологов образования России. Анализ опыта реализации региональных программ оказания психолого-педагогической помощи детям направлен на совершенствование научного и методического обеспечения психолого-педагогической деятельности. Количество поданных на конкурс программ и технологий демонстрирует место и роль коррекционно-развивающей, профилактической и просветительской работы педагогов-психологов.